2021
DOI: 10.1002/ps.6633
|View full text |Cite
|
Sign up to set email alerts
|

Non‐target‐site resistance mechanism of barnyardgrass [Echinochloa crus‐galli (L.) P. Beauv.] to florpyrauxifen‐benzyl

Abstract: BACKGROUND Florpyrauxifen‐benzyl (FPB) is an arylpicolinate herbicide (Group IV) for barnyardgrass control in rice. One susceptible (Sus) and three putative FPB‐resistant (R1, R2, and R3) barnyardgrass biotypes were selected based on resistant/susceptible (R/S) ratios obtained from dose–response tests and used to investigate the potential resistance mechanisms. RESULTS Based on visual control results, the R/S ratios of barnyardgrass biotypes R1, R2, and R3 were 60‐, 33‐, and 16‐fold greater than the Sus standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
(54 reference statements)
2
19
1
Order By: Relevance
“…Florpyrauxifen-benzyl (Loyant® herbicide with Rinskor ™ active, Indianapolis, IN, USA) was introduced to the market in 2018 and was widely adopted for selective control of E. crus-galli in rice fields (Epp et al 2016). In the winter following the commercial launch of florpyrauxifen-benzyl, a greenhouse screen performed across multiple E. crus-galli populations from the midsouthern United States identified populations with resistance to florpyrauxifen-benzyl (Hwang et al 2022b;Miller et al 2018). A follow-up study associated the resistance mechanism to reduced foliar absorption and decreased activation of florpyrauxifen-benzyl into its acid form in resistant plants (Hwang et al 2022a(Hwang et al , 2022b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Florpyrauxifen-benzyl (Loyant® herbicide with Rinskor ™ active, Indianapolis, IN, USA) was introduced to the market in 2018 and was widely adopted for selective control of E. crus-galli in rice fields (Epp et al 2016). In the winter following the commercial launch of florpyrauxifen-benzyl, a greenhouse screen performed across multiple E. crus-galli populations from the midsouthern United States identified populations with resistance to florpyrauxifen-benzyl (Hwang et al 2022b;Miller et al 2018). A follow-up study associated the resistance mechanism to reduced foliar absorption and decreased activation of florpyrauxifen-benzyl into its acid form in resistant plants (Hwang et al 2022a(Hwang et al , 2022b.…”
Section: Introductionmentioning
confidence: 99%
“…In the winter following the commercial launch of florpyrauxifen-benzyl, a greenhouse screen performed across multiple E. crus-galli populations from the midsouthern United States identified populations with resistance to florpyrauxifen-benzyl (Hwang et al 2022b;Miller et al 2018). A follow-up study associated the resistance mechanism to reduced foliar absorption and decreased activation of florpyrauxifen-benzyl into its acid form in resistant plants (Hwang et al 2022a(Hwang et al , 2022b. The same study found no mutations in the auxin receptors TIR1 and AFB5, although most cases of target-site resistance to synthetic auxins are associated with the Aux/IAA co-receptor proteins (Figueiredo et al 2022;Todd et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the greatest differences (2.2–3.4 times) in CyA residue between S and R biotypes were observed at 6 h after herbicide treatment. Referring to results of previous studies performed for cyhalofop-butyl, , imazamethabenz-methyl, or florpyrauxifen-benzyl, , reduced production or rapid degradation of CyA in R biotypes likely contributes to conferring CyB resistance to barnyardgrass. Similarly, Deng et al reported that rapid metabolism of an active form CyA can contribute to evolving the CyB resistance in Chinese sprangletop verified with no mutation in genes encoding ACCase proteins.…”
Section: Resultsmentioning
confidence: 68%
“…Echinochloa spp. are weedy plants that have evolved resistance to several herbicide classes [ 18 , 19 , 20 , 21 ]. To minimize the use and risk of herbicides, reducing herbicide doses in chemical weed control has been extensively investigated in recent years and has provided sufficient weed control and desirable yield [ 22 ].…”
Section: Introductionmentioning
confidence: 99%